Juvenile-onset recurrent respiratory papillomatosis - Karwowska, Anna; Wojno, Aleksandra; Dorobisz, Karolina (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Juvenile-onset recurrent respiratory papillomatosis (JORRP) is a rare disease caused by an infection of human papillomavirus (HPV) – most commonly types 6 and 11. These types of HPV are vaccine-preventable. The virus is transmitted vertically. Human papillomavirus can alter immune response by reducing interferon-γ and interleukin-2 expression. Most JORRP patients develop symptoms before the age of 5 years. In severe cases this disease can lead to airway obstruction or malignant transformation. The treatment primarily consists of surgery as well as intralesional or systemic bevacizumab therapy or adjuvant therapy. Patients who develop symptoms at a younger age usually need more surgeries than older patients with JORRP. To reduce the incidence rate of JORRP, HPV vaccination is recommended.